Constructing and Standardizing Compound Tests (Physical _ Skill) According to Phosphate Energy System for National Center for Gifted in Handball Players aged (15 - 17) Years Old - Mustafa Essa Eqab; Hamid Saleh Mahdi (College of Physical Education and Sport Sciences, 2021)
The research aim at constructing and standardizing compound tests (skill - physical) according to the phosphate energy system for the national center for gifted handball players aged (15 - 17) years old. The researchers used the descriptive method on (60) handball players from the national center for gifted in handball. Four tests were selected and a pilot study was conducted followed by the tests and the data was collected and treated using proper statistical operations to conclude that compound tests give a realistic evaluation for handball performance. Finally, the researcher recommended using these tests on regular bases for players' selection as well as making other tests on other abilities and skills.